Analisis Yuridis atas Penegakan Hukum Pidana Ekonomi pada Kasus Hacker Bjorka di Indonesia - Septa Merando BP (Jurnal Hukum Lex Generalis, 2025)
This research abstract discusses the criminal prosecution of economic crimes related to the hacker Bjorka case, involving the illegal theft and sale of personal data in Indonesia. The study employs a normative juridical approach focusing on the legal construction under the Electronic Information and Transactions Law and the Personal Data Protection Law. The analysis reveals that Bjorka’s actions constitute cybercrime subject to penalties of up to 12 years imprisonment. Victims of data breaches are legally protected and entitled to compensation. Effective law enforcement and stringent data protection are essential to addressing increasingly complex digital economic crimes in Indonesia. The study highlights the need for synergy between law enforcement, regulators, and the public to ensure data security and uphold justice.